In silico analysis decodes transthyretin (TTR) binding and thyroid disrupting effects of per- and polyfluoroalkyl substances (PFAS) - Dharpure, Rupal; Pramanik, Subrata; Pradhan, Ajay (Archives of Toxicology, 2023)
Transthyretin (TTR) is a homo-tetramer protein involved in the transport of thyroid hormone (thyroxine; T4) in the plasma and cerebrospinal fluid. Many pollutants have been shown to bind to TTR, which could be alarming as disruption in the thyroid hormone system can lead to several physiological problems. It is also indicated that the monomerization of tetramer and destabilization of monomer can lead to amyloidogenesis. Many compounds are identified that can bind to tetramer and stabilize the tetramer leading to the inhibition of amyloid fibril formation. Other compounds are known to bind tetramer and induce amyloid fibril formation. Among the pollutants, per- and polyfluoroalkyl substances (PFAS) are known to disrupt the thyroid hormone system. The molecular mechanisms of thyroid hormone disruption could be diverse, as some are known to bind with thyroid hormone receptors, and others can bind to membrane transporters. Binding to TTR could also be one of the important pathways to alter thyroid signaling. However, the molecular interactions that drive thyroid-disrupting effects of long-chain and short-chain PFASs are not comprehensively understood at the molecular level. In this study, using a computational approach, we show that carbon chain length and functional group in PFASs are structural determinants, in which longer carbon chains of PFASs and sulfur-containing PFASs favor stronger interactions with TTR than their shorter-chained counterparts. Interestingly, short-chain PFAS also showed strong binding capacity, and the interaction energy for some was as close to the longer-chain PFAS. This suggests that short-chain PFASs are not completely safe, and their use and build-up in the environment should be carefully regulated. Of note, TTR homologs analysis suggests that thyroid-disrupting effects of PFASs could be most likely translated to TTR-like proteins and other species.